Clinico-pathological Profile of Kidney Biopsy Patients in a Tertiary Hospital of Central Nepal - Ghimire, M.; Vaidya, S.; Upadhyay, H. P. (Kathmandu University Medical Journal, 2020)
Background Kidney biopsy is an important diagnostic tool in Nephrology. As of now, we don’t have a central kidney biopsy registry in our country and there are many studies showing heterogeneous patterns of pathologies observed in the country. We thought of looking on the clinico-pathological profile of kidney biopsy patients prevailing in our centre. Objective This study was carried out with an objective to know the clinico-pathological profile of kidney biopsy patients prevailing in our centre. Method This was a hospital based, prospective, observational study carried out in a tertiary teaching hospital of Chitwan over a period of 3 years from May 2016 to April 2019. All the consecutive kidney biopsy patients were included in the study. The indication of kidney biopsies were the standard indication based on clinical presentation and investigations. The patient`s demographic profile, indication of kidney biopsy and histological patterns were studied and analysed using appropriate statistical tools. Result A total of 210 kidney biopsies were analysed over a period of three years, that makes around 5-6 biopsies per month. The mean age of the patient was 35.7 ± 14.9 years. Male were 106 (50.5) and females were 104 (49.5) with male to female ratio of 1.01. The average number of glomeruli was 23.4 ± 11.0. The commonest indication of kidney biopsy and histological pattern were nephrotic syndrome 56 (26.7) and IgA nephropathy 51 (24.2) respectively. Among nephrotic syndrome group, the commonest histological pattern was minimal change disease 21 (37.5). Non-diabetic kidney diseases in diabetes were seen in eight (53.4) diabetic patients making it a significant problem in diabetes and the commonest histological pattern in them were minimal change disease and idiopathic cresentic glomerulonephritis two (13.3) each. Conclusion The commonest indication and histological pattern of the kidney biopsy were nephrotic syndrome 56 (26.7), and IgA Nephropathy 51 (24.2) respectively. Non-diabetic kidney diseases in diabetes were seen in eight (53.4) of the diabetic patient making it a significant problem in diabetes and the commonest histological pattern in them were minimal change disease and idiopathic cresentic glomerulonephritis two (13.3) each.